Weisner And Hartford, Eds., American Portraits - Biographies In United States History - Lookingbill, Brad (Teaching History: A Journal of Methods, 1998)
Teaching historians often assign biography to supplement reading lists for the introductory survey classroom, even though selecting which life to share might be a difficult process. Biography represents a unique form of history and literature, inviting a reader to come to terms with the significance of human agency. Indeed, a biography possesses the potential to reveal how a particular person influenced and was influenced by broader historical forces.